2020
DOI: 10.3389/fvets.2020.00569
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Phytogenic Modulates the Rumen Bacteria Composition and Milk Fatty Acid Profile of Water Buffaloes

Abstract: This study was aimed to evaluate the effect of a mixed phytogenic (MP) on rumen bacteria and their potential association with rumen fermentation and milk yield parameters in water buffaloes. Twenty Murrah buffaloes were fed a basal diet (consisting of maize silage, brewers' grains, and concentrate mixture) for 6 weeks supplemented with 0 (control), 15 (MP15), 25 (MP25), and 35 (MP35) g of mixed phytogenic/buffalo per d. The mixed phytogenic contained fennel (seeds), ajwain (seeds), ginger (tubers), Swertia chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 101 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…Plants and fruits naturally contain polyphenols such as tannins, flavonoids, and other phytochemicals that have antioxidant, anti-inflammatory, antibacterial, antiviral, and antiparasitic properties that can boost the health and productivity of animals [1][2][3]. In addition, mixing phytogenics or tannins in ruminant animals' diets has been found to modulate ruminal biohydrogenation, resulting in increased levels of health-promoting fatty acids in milk [4][5][6][7][8], such as very long chain n-3 fatty acids (FA) including eicosapentaenoic acid (EPA; 20:5n-3) and docosahexaenoic acid (DHA; C 22:6 ). Moreover, tannins, when administered at low concentrations, can increase the production of microbially generated odd and branched FAs (OBCFA) (iso-and ante-iso and uneven chain FA) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Plants and fruits naturally contain polyphenols such as tannins, flavonoids, and other phytochemicals that have antioxidant, anti-inflammatory, antibacterial, antiviral, and antiparasitic properties that can boost the health and productivity of animals [1][2][3]. In addition, mixing phytogenics or tannins in ruminant animals' diets has been found to modulate ruminal biohydrogenation, resulting in increased levels of health-promoting fatty acids in milk [4][5][6][7][8], such as very long chain n-3 fatty acids (FA) including eicosapentaenoic acid (EPA; 20:5n-3) and docosahexaenoic acid (DHA; C 22:6 ). Moreover, tannins, when administered at low concentrations, can increase the production of microbially generated odd and branched FAs (OBCFA) (iso-and ante-iso and uneven chain FA) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The type and abundance of bacteria will also affect the characteristics of the ruminal fatty acids. Butyrivibrio sp is reliable for the hydrolysis of phospho-and galactolipids, while Anaerovibrio lipolytic correlated with caprylic caproic and lauric fatty acid production acids [26] [27]. The study reported that caproic and lauric levels decreased significantly (P<0.05) with galangal EO (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Petric et al [ 21 ] noticed that herbal mixture supplementation in lambs affected the bacterial population and the abundance of Ruminococcus and Fibrobacter . In water buffalo, Hassan et al [ 22 ] reported that phytochemicals mixtures increased the relative abundance of phylum Firmicutes and Proteobacteria, while the relative abundances of Bacteroidetes and Spirochaetes besides genus Prevotella were declined. Kholif et al [ 8 ] indicated that herbal mixture increased total VFA and propionic acid besides the relative abundances of propionate-producing bacteria such as family Prevotellaceae and Veillonellaceae, and declined the methane-producing archaea, Methanobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%